2012
DOI: 10.1371/journal.pone.0030052
|View full text |Cite
|
Sign up to set email alerts
|

Novel Protocol for the Chemical Synthesis of Crustacean Hyperglycemic Hormone Analogues — An Efficient Experimental Tool for Studying Their Functions

Abstract: The crustacean Hyperglycemic Hormone (cHH) is present in many decapods in different isoforms, whose specific biological functions are still poorly understood. Here we report on the first chemical synthesis of three distinct isoforms of the cHH of Astacus leptodactylus carried out by solid phase peptide synthesis coupled to native chemical ligation. The synthetic 72 amino acid long peptide amides, containing L- or D-Phe3 and (Glp1, D-Phe3) were tested for their biological activity by means of homologous in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…Serrano et al (Serrano et al, 2003) demonstrated that, in P. leptodactylus, a more prominent increase of osmolarity and sodium concentration in the circulation was caused by D-CHH than by L-CHH. Finally, a different time course and intensity of increase in circulating glucose was triggered by the two isomers in P. leptodactylus (Lebaupain et al, 2012;Mosco et al, 2012;Serrano et al, 2003). Earlier hyperglycemia was induced by L-CHH but it lasted for a shorter period and was less intensive than that induced by D-CHH.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Serrano et al (Serrano et al, 2003) demonstrated that, in P. leptodactylus, a more prominent increase of osmolarity and sodium concentration in the circulation was caused by D-CHH than by L-CHH. Finally, a different time course and intensity of increase in circulating glucose was triggered by the two isomers in P. leptodactylus (Lebaupain et al, 2012;Mosco et al, 2012;Serrano et al, 2003). Earlier hyperglycemia was induced by L-CHH but it lasted for a shorter period and was less intensive than that induced by D-CHH.…”
Section: Introductionmentioning
confidence: 91%
“…A broader time scale of 48 h was examined in experiment 2 and results are presented in supplementary material Fig. S1, revealing the typical time course and intensity caused by each of the applied isomers (Mosco et al, 2012).…”
Section: Morphology and Physiology Of The Experimental Femalesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although P. leptodactylus is not considered a model organism, it is one of the most studied species among decapods with about 143 published papers regarding its physiology [1], [36], [37], [38], its resistance to different types of pollution and stress conditions [39], [40], [41] and concerning the cHH and its variety of functions [42], [43], [44], [45]. Unfortunately this variety of studies does not reflect the fast progress of genomics and transcriptomics.…”
Section: Introductionmentioning
confidence: 99%